The History of the Communist Party of Great Britain Volume 2 : 1925-1926 The General Strike - Klugmann, James (Book collections on Project MUSE., 2015)
This second in the six volume series covers the years of the General Strike, and includes a detailed examination of the policies, successes and failings of Communists and the militant left generally.